Organic Foulants Characteristics in Membrane Bioreactor - Aryal, R. K.; Vigneswaran, S.; Lebegue, J.; Shon, H. K.; Kandasamy, J.; Heran, M.; Grasmick, Alain (Journal of Applied Membrane Science & Technology, 2017)
A laboratory scale side stream membrane bioreactor system with flat sheet membrane was operated for 5–days run at three different aeration rates (100, 200 and 300 L/h). The organic foulants deposited on the membrane surface was studied after extraction with 5% NaOH solution using three spectroscopic techniques. The IR spectra showed no distinct similarity in peaks among the three. The fluorescence spectra showed increase of soluble microbial products in foulant with decrease of aeration rate. This was supported by the size exclusion chromatography in which biopolymers concentration in fouling decreased with increasing aeration rate.